Modul Ajar Projek Penguatan Profil Pelajar Pancasila Berbasis Tema Kearifan Lokal untuk Meningkatkan Kemampuan Literasi Budaya di SMA Negeri 1 Babat, Lamongan - Anindita Surya Mahanani; Agus Suprijono; Sugeng Harianto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The independent curriculum is a new color in learning activities and also as a means of improving the quality of education after the Covid-19 pandemic. The implementation is based on Permendikbudristek number 56 of 2022. The characteristic of the independent curriculum is the cultivation of character values of the Pancasila Student Profile Strengthening Project whose actualization is packaged in Project-based learning. The learning is a Project for Strengthening the Profile of Pancasila Students in which there are several themes, one of which is the theme of local literacy. This study aims to see how the implementation of the Teaching Module of the Pancasila Student Profile Strengthening Project on the Theme of Local Wisdom in improving students' cultural literacy skills at SMA Negeri 1 Babat, Lamongan which has the status of an independent school has changed. As a result, the implementation showed that the teaching module of the Pancasila student profile strengthening project with the theme of local wisdom was able to improve cultural literacy skills by looking at the average score gain, namely before treatment of 77 and after treatment of 88.3. Then the percentage of implementation that has been carried out well and the positive response of students to these learning activities.